The Effect of Teams Games Tournament (TGT) Models Containing Science Literacy on Students’ Learning Competencies in Ecology Material at Junior High School 10 Padang - Winda Tri Wahyuni; Rahmadhani Fitri; Ganda Hijrah Selaras; Syamsurizal Syamsurizal (Universitas Negeri Padang, 2019)
This research is based on the problems that exist at senior high school 10 Padang, namely the learning model that is less varied, students' learning competencies are still low. Efforts that can be done are applying the learning model Teams Games Tournament (TGT) with scientific literacy in the Ecology material at senior high school 10 Padang. The purpose of this study was to determine the effect of the application of the learning model that Teams Games Tournamen (TGT) contained scientific literacy to the learning competencies of Grade X students of senior high school 10 Padang. This research is an experimental research with randomized control group posttest only design. The study population is the students of Grade X senior high school 10 Padang 2018/ 2019 academic year which spread into eight classes. Sampling research using simple random sampling. The results were selected class X.8 as experimental class and class X.5 as a control class. The hypothesis in this study was tested using the t-test. The results of the study using the t-test it can be concluded that the competency of students' knowledge of the value of tcount 3.34> ttable 1.67, in the competency attitude the value of tcount 2.15> ttable 1.67, the competency attitudes tcount 5.26> ttable 1.67, and the competence of value skills tcount 1.95> ttable 1.67. This shows that the hypothesis is accepted. So, it can be concluded that the application of TGT models with scientific literacy can improve the competency of knowledge, attitudes, and skills of class X students of senior high school 10 Padang.